GAMBARAN PERILAKU PROSOSIAL SISWA KELAS VII SMP NEGERI 1 CIMAHI - Ai Solihat; Euis Eti Rohaeti; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The purpose to be achieved in this study is to describe the prosocial behavior of students at SMP Negeri 1 Cimahi. This type of research is descriptive quantitative. The subjects in this study were students of SMP Negeri 1 Cimahi. Subjects taken were 24 people. The data in this study were obtained through a closed questionnaire. The results illustrate that from the six aspects of prosocial behavior in general it can be described that the prosocial behavior of students of SMP Negeri 1 Cimahi is in the high category, especially in the aspects of helping, generosity and cooperation with a percentage of more than 48%.Keywords: Prosocial Behavior, Junior High School Students.